Legalitas Pengaturan Kepesertaan BPJS Kesehatan Sebagai Syarat Pelayanan Publik - Moh. Hasyim; Nurmalita Ayuningtyas Harahap (Universitas Widya Gama Malang, 2023)
The purpose of this study is to find out and analyze how the legality of BPJS Health membership arrangements is a condition of public service. The research method used covers, first, this type of research is normative juridical research which is based on primary and secondary legal materials. Second, the review is carried out using a conceptual approach (conceptual approach) and statutory approach (statute approach). Third, this research is a library research. The results of this study state that administrative sanctions in the form of not providing public services because they are not registered as BPJS participants have fulfilled the legality principle, because they have been regulated in Article 17 of the BPJS Law which is then regulated further in PP 86 Number 2013, while Presidential Instruction 1 of 2022 is a guideline that apply internally to implement the two regulations. However, in accordance with the principle of legality, based on the attribution of authority granted by Article 17 paragraph (5) of the BPJS Law, PP 86 Number 2013 only regulates the procedure for imposing administrative sanctions, does not regulate the determination of membership in the JKN program as a requirement for obtaining public services as well as mentioning the types of The types of public services referred to, and both of these things should be regulated in law.